Problems in bread making - Finlayson, Stella (My University, 1907)
Introduction: Bread is no doubt the most essential food of man. It takes the most important part in the nutrition of all classes of people. Bread is not so highly valued because of the ease of preparation but because of its nutriment, palatability, and digestibility. In it are all the substances necessary for the nutrition of man, namely; carbohydrates, proteids, fats, and mineral salts. The carbohydrates and proteids are present in about the right proportion, but the fats are deficient. Bread is one of the most constant sources of nitrogen in the daily diet. The gluten of the flour furnishes the greater part of the nitrogen. The proportion of fat can easily be raised by the use of butter. Another reason bread is so universally used is because of its cheapness. Considering the materials used it is cheap compared to other foods because it supplies all the necessary elements and does not require the addition of other foods to make a nourishing diet. Properly made bread is palatable by itself, and is made more so by the addition of butter, or when eaten with other foods. Bread making is by no means a modern art, it was known some 3000 B.C. Probably the first grain cultivated for use in bread making was barley. Next came the use of wheat, which was cultivated in Egypt 4000 B.C. and in China 3000 B.C. The hone of the barley plant is in Asia Minor, that of the wheat plant in Central Asia. The use of wheat in bread making is more universal than barley, especially in the more advanced nations. It could be truthfully said that through the cultivation of these grains civilization has been fostered. The aborigines were nomadic because they were forced to change their habitations as the source of food became exhausted. When they learned to cultivate these grains which could be stored they could remain in one place, and thus gain advantages over those who had remained nomadic. Because of this the discovery of the use of the cereals in bread making has been described by the ancients as a gift of God. We find many references to bread…
Citation: Finlayson, Stella. Problems in bread making. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Bread; Making Bread; Bread Composition; Food Processing; Problems in Bread Making; Theses